Suitability of Biofuels Production on Commercial Scale from Various Feedstocks: A Critical Review. Issue 5 (25th July 2022) - Sarwer, Asma; Hussain, Murid; Al‐Muhtaseb, Ala'a H.; Inayat, Abrar; Rafiq, Sikander; Khurram, M. Shahzad; Ul‐Haq, Noaman; Shah, Noor Samad; Alaud Din, Aamir; Ahmad, Ishaq; Jamil, Farrukh
Abstract: The growing demand for energy resources and the increase in greenhouse gas (GHG) emissions has given biofuels a lot of attention. Liquid biofuels can be a significant alternative for the transport sector. Generally, biofuels are categorized into four generations based on the feedstock. This review reports the availability, economic feasibility, and potential of biofuel feedstock in global scenario. Feedstock for first‐generation biofuel comprises edible resources impacting the food supply. Second generation biofuels are based on different residual materials and nonedible fuel crops. Cost and technological limitations for commercialization hinders this option. Microalgae are the feedstock for third generation biofuels providing the highest yield compared to the other two generations. A scale‐up to commercial level is not possible as this requires further development. Genetically modified microorganisms are used as a feedstock for fourth generation biofuel production with the highest possible yield. Third and fourth generation biofuels have potential to replace fossil fuels. This review recommends certain suggestions for sustainable biofuel production. Abstract : The growing demand for energy resources and the increase in greenhouse gas emissions has given biofuels a lot of attention. Here the availability, economic feasibility, and potential of biofuel feedstock in global scenario are reported and certain suggestions for sustainable biofuel production are recommended.